Heavy metals impact environmental capacity of oasis soils in Qinghai-Tibet Plateau dry zone - Siqi Han; Bin Wang; Zhen Yao; Lu Dai; Youning Wei; Yao Niu; Ling Qian (Scientific Reports)
Abstract The Tibetan Plateau is known as the “third pole of the world,” and plateau oases are a key component of plateau ecosystems. Under natural conditions, the ecosystems on the Tibetan Plateau contain relatively low levels of heavy metals. However, the overexploitation of resources by humans for production and living has affected the quality of soils in the Qinghai-Tibet region, whereby the environmental capacity is decreasing. The oases in the arid zone of Delingha-Wulan County were selected as the study area for determining the environmental capacity of soil heavy metals in the Tibetan Plateau. The results indicated that the six key heavy metals in the study region ranked in the following overall order of static environmental capacity: Zn > Pb > Cu > As > Hg > Cd. High values of the elemental residual capacity occurred mainly in the Chachaxiangka area, whereas low values occurred mainly in the Wulan area. The geological background of the research area had a statistically significant on the residual capabilities of all six elements. Except for Pb, the other five elements were significantly affected by soil type and land use. This study revealed the soil-carrying capacity of oases in arid zones. The findings reported herein provide a scientific foundation for safeguarding the ecosystem in the oases of the arid zone in the Qinghai-Tibetan region.